2021
DOI: 10.1364/ol.417148
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired wrinkle microstructures for random lasing governed by surface roughness

Abstract: A method for fabricating bio-inspired scattering substrates based on polydimethylsiloxane (PDMS) for spatially incoherent random lasing is presented. The leaves of monstera and piper sarmentosum plants are used to mold PDMS polymer to form wrinkle-like scattering substrates, which are then used with a liquid gain medium for random lasing. Scattering is attributed to the surface roughness ( S a ) of the samples. The rougher sample with 5.2 µm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In real tissue samples, biocompatible fluorescent anticancer drugs and organic dyes could be used to generate random lasing [13,14]. The phantom tissue sample was initially investigated for lasing using a standard random lasing experimental setup [33]. 532 nm second harmonic emission from an Nd:YAG laser (VIBRANT 355 II, OPOTEK Inc., Carlsbad, CA, USA) running at 10 Hz repetition rate and 5 ns pulse duration was used as the excitation source.…”
Section: Phantom Tissue Model Of Tumor Polypmentioning
confidence: 99%
See 1 more Smart Citation
“…In real tissue samples, biocompatible fluorescent anticancer drugs and organic dyes could be used to generate random lasing [13,14]. The phantom tissue sample was initially investigated for lasing using a standard random lasing experimental setup [33]. 532 nm second harmonic emission from an Nd:YAG laser (VIBRANT 355 II, OPOTEK Inc., Carlsbad, CA, USA) running at 10 Hz repetition rate and 5 ns pulse duration was used as the excitation source.…”
Section: Phantom Tissue Model Of Tumor Polypmentioning
confidence: 99%
“…Recent research demonstrated how surface corrugations on polymer substrates affect random lasing [33]. Distinct features were observed in the lasing spectra, threshold, and linewidth characteristics with surface roughness variations.…”
Section: Introductionmentioning
confidence: 99%
“…The structural confinement of disorder plays a crucial role in random lasing emission 19 . Given its sensitive dependence on surface roughness 20 , random lasing provides a distinctive approach for sensing tumor polyps by inspecting the surface variations associated with tumor progression. The random laser-based diagnostic technique is proposed to complement colonoscopy, particularly for identifying smaller and sessile polyps, utilizing their surface variations as a probing parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to the random distribution of the scattered particles in a random laser system, the lasing spectrum is varied and unstable. In order to control the random laser emission, scientists have utilized a variety of materials to design random lasers, including semiconductor [5], liquid crystal [6,7], metal nanostructure [8,9], thin film [10], wrinkled graphene oxides [11], waveguide structure [12,13] and even perovskite single crystal [14].…”
Section: Introductionmentioning
confidence: 99%